2012
DOI: 10.1111/j.1365-2435.2012.02029.x
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of stress: effects of the social environment

Abstract: Summary Many aspects of the social environment affect hypothalamic‐pituitary‐adrenal (HPA) axis function and increase circulating glucocorticoid concentrations. In this review, we examine the relationships between the social environment and the function of the HPA axis in vertebrates. First, we explore the effects of the social environment on glucocorticoid secretion in territorial (primarily non‐social) species, with an emphasis on the effects of variation in population density, as modified by environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
374
3
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(399 citation statements)
references
References 162 publications
9
374
3
3
Order By: Relevance
“…Meerkats forage in cohesive groups and therefore, within groups, individuals experience similar local environmental conditions including predation pressure.Sex, body condition, reproductive stage (Keay et al, 2006;Millspaugh and Washburn, 2004), and social context (Creel et al, 2013) are all likely to affect both adrenal activity and time required to respond to potential predators. In meerkats, dominance status (Carlson et al, 2004) and the presence of pups can influence plasma GC , and reproductive stage affects mean fGC concentrations (Barrette et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meerkats forage in cohesive groups and therefore, within groups, individuals experience similar local environmental conditions including predation pressure.Sex, body condition, reproductive stage (Keay et al, 2006;Millspaugh and Washburn, 2004), and social context (Creel et al, 2013) are all likely to affect both adrenal activity and time required to respond to potential predators. In meerkats, dominance status (Carlson et al, 2004) and the presence of pups can influence plasma GC , and reproductive stage affects mean fGC concentrations (Barrette et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Harvey et al, 1984, Bush and Hayward, 2009, Zanchi et al, 2010, Goymann 2012), which in turn, can affect individuals" response to internal and external stimuli (Dowle et al, 2012). Under challenging conditions, such as food deprivation, social instability or predation risk (Dallman et al, 1993;Creel et al, 2009Creel et al, , 2013 adrenal activity increases the production of glucocorticoids (GCs) to mobilize energy and resolve stressful stimuli (Harvey et al, 1984;McEwen and Wingfield, 2003;Wingfield, 2005;Romero et al, 2009). In turn, GCs can modulate the intensity of behavioral responses to stimuli such as presence of predators (Sapolsky et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Specific individual characteristics such as social status, body condition and territory quality can also influence Egained in terms of access to food and variation of quality with habitat. Given these diverse contributions to energy available to the individual we consider the cumulative resources available (Ecr) that ultimately affect an individual and are critical for the allostasis concept but are largely ignored in other discussions of allostasis and reactive scope [14,16,[41][42][43]. In the absence of considering Ecr, then the assumption must be that food and access to it is ad libitum.…”
Section: A New Take On the Biological-based Approachmentioning
confidence: 99%
“…Because most males compete for opportunities to fertilize females (30) the focus of studies investigating correlates of male physiological stress have historically been on reproductive competition and hierarchical status (31)(32)(33). Nevertheless, recent and increasing evidence has shown that males of some vertebrate species also form strong social bonds that can enhance their fitness (refs.…”
mentioning
confidence: 99%